Procrastination and Parental Support as Determinants of Academic Stress in Nursing Students - Mustofa, Hanif Furqon; Sulistyowati, Dwi Ariani; Caturini, Endang (Interest : Jurnal Ilmu Kesehatan, 2023)
Background: The Covid-19 pandemic has resulted in changes in learning methods from face-to-face to online, which has an impact on increasing the academic stress of nursing students. Academic stress is the pressure experienced in the academic environment and is influenced by internal and external factors.  This study aims to identify factors associated with nursing students' academic stress levels during online lectures in the Covid-19 pandemic. Methods: The research approach was quantitative with correlational analytic design and cross-sectional method. The research sample was selected by random sampling, involving 256 respondents. Data were collected using a Likert scale-based questionnaire and analysed with Chi-Square and Kendall's Tau statistical tests.   Results: Gender has no relationship to the level of academic stress of nursing students (p = 0.164); while procrastination is related to the level of academic stress with a moderate correlation and positive relationship direction (p = <0.001; r = 0.285). In addition, parental social support also affects the level of academic stress with a moderate correlation and negative relationship direction (p = <0.001; r = 0.329).  Conclusion: Factors associated with academic stress levels of nursing students are procrastination and parental social support. It is recommended that educational institutions implement targeted interventions to minimize academic procrastination and strengthen parental support systems as strategic efforts to manage academic stress among nursing students.